Meningoencephalitis associated with GAD65 autoimmunity - Kuang, Zuying; Baizabal-Carvallo, José Fidel; Mofatteh, Mohammad; Xie, Sifen; Pan, Mengqiu; Ye, Jinlong; Zhou, Lihua; Yang, Shuiquang; Wang, Zhanhang; Chen, Yimin; Li, Yaqin (Frontiers in Immunology, 2023)
Background: Encephalitis has been recognized in patients with autoimmunity related to the 65-kDa isoform of glutamic acid decarboxylase (GAD65) antibodies; however, patients with meningoencephalitis associated to those antibodies have been rarely identified in the medical literature. We aimed to define the frequency, clinical features, response to therapy and functional outcomes of patients with meningoencephalitis associated with GAD antibodies. Methods: We retrospectively studied consecutive patients attending a tertiary care center for evaluation of an autoimmune neurological disorder from January 2018 to June 2022. The modified Rankin Scale (mRS) was used to assess the functional outcome at the last follow-up. Results: We evaluated 482 patients with confirmed autoimmune encephalitis during the study period. Four among 25 patients with encephalitis related to GAD65 antibodies were identified. One patient was excluded owing to the coexistence of NMDAR antibodies. Three male patients aged 36, 24 and 16 years had an acute (n=1) or subacute (n=2) onset of confusion, psychosis, cognitive symptoms, seizures or tremor. No patient had fever or clinical signs of meningeal irritation. Mild pleocytosis (<100 leukocytes/106) was identified in two patients, whereas one patient had normal CSF. Following immunotherapy with corticosteroids (n=3) or intravenous immunoglobulin (n=1), significant improvement was observed in all three cases, achieving a good outcome (mRS 1) in all cases. Conclusion: Meningoencephalitis is an uncommon presentation of GAD65 autoimmunity. Patients present with signs of encephalitis but with meningeal enhancement. Patients have good outcomes.